The Effects of On-time, Delayed and Early Kindergarten Enrollment on Children's Mathematics Achievement: Differences by Gender, Race, and Family Socio-economic Status - Dagli, Ummuhan Yesil; Jones, Ithel (EDAM, 2012)
This study was an examination of the effect of delayed, early, and on-time kindergarten enrollment on children's kindergarten mathematics achievement. Central for this study was to explore if the relationship between the kindergarten enrollment status and mathematics achievement varies by children's gender, race, and family SES status. It used a nationally representative sample of ECLS-K data collected in the United States of America. On average, findings of this study suggested that children with delayed enrollment in kindergarten had stronger mathematics skills than children with on-time enrollment in kindergarten, who had stronger skills than children with early enrollment. However, this pattern of relationship appeared to be different for children from lower socioeconomic background and children from racial minority groups by their gender.
Keywords: Kindergarten Mathematics Achievement; Age of Kindergarten Entry; Socio-Demographic Factors; ACADEMIC-ACHIEVEMENT; SCHOOL READINESS; ENTRANCE AGE; CHRONOLOGICAL AGE; EARLY RETENTION; ENTRY; CAROLINA; SCORES; TESTS; Education & Educational Research